Some Remarks on Fixed Point Theorems for Interpolative Kannan Contraction - Youssef Errai; El Miloudi Marhrani; Mohamed Aamri (Journal of Function Spaces)
In this paper, we use interpolation to obtain fixedpoint and common fixed point results for a new type of Kannan contraction mappings in complete metric and b-metric spaces. Our results extend and improve some results on fixed point theory in the literature. We also give some examples to illustrate the given results.